A modified technique of using digital technology to fabricate surgical obturator in patients with limited mouth opening - Divyajoti Das; Rekha Gupta; Shubhra Gill; Aishwarya Saini (Journal of Oral Biology and Craniofacial Research, 2023)
This article presents a digital technique for the fabrication of an immediate surgical obturator for a patient with decreased mouth opening planned for maxillectomy. The amalgamation of pre-operative Cone Beam Computed Tomography (CBCT) data and 3D printing allowed for the fabrication of the immediate surgical obturator without conventional pre-surgical diagnostic impression. The surgical obturator was placed in position intraorally post tumor resection to complete the obturation. The procedure followed led to an accurate fit of the prosthesis without any need for relining during surgery.